Public policy and the digital deadline: The implementation of the Digital Addressable System (DAS) in West Bengal. (1st June 2019) - Pandit, Sushmita
The introduction of the mandatory Digital Addressable System (DAS) with strict, phase-wise deadlines for different provinces within India has compelled us to reconsider not only the television apparatus itself but also broadcast policies, television industry, content and reception. The introduction of DAS can be posited within a series of similar public policies starting from the Satellite Instructional Television Experiment (SITE) project in 1975 to the more recent Unique Identification Authority of India (UIDAI) or Aadhaar project and Digital India campaign, all folded into the developmental rhetoric of the welfare state. The rollout of DAS provides the site to explore the relationship between the government, neo-liberal market and digital technologies that underscores the contradictions which are constitutive of modernity, and invests in the study of the neo-liberal cultural sites of statist intervention. Within this conceptual framework, this article would focus on West Bengal as a case in point to read the implementation of mandatory DAS both as a site of hegemonic projects embodying promises of neo-liberal development and of the incongruities that are inherent in them. While the union government claimed that any cable television service provider who does not switch to digital signal within deadline can be penalized and the equipment confiscated, the state Government said that they would launch an agitation if analogue cable signals were blacked out after the deadline for cable digitalization and thus, the deadline was extended for several months. The confrontation over cable digitalization in West Bengal offers a site to explore in what way, contrary to its typical image of a fully automated digital ecosystem of governance, as the modern states would like to conceive, it is loaded with internal contradiction. My inquiry moves across a range of discursive locations and registers, aiming to explore in what way various local stakeholders negotiate in this policy implementation? How does DAS help theorization of a changing relationship between the market, digital technology and the developmental modern? While raising these questions, this article would try to explore in what way DAS can be located within the historical trajectory of techno-cultural rhetoric of public policy and how it invests in the shifting political economy of broadcasting in India.